Interactions of a flexible insert in ideal open and channel flows - Burke, Meagan Alison (Curtin University, 2015)
Methods to study the behaviour of a flexible insert comprising one wall of inviscid open and channel flows are developed. Small insert deflections, transient growth and large insert deflections are considered. Findings include; (i) reducing channel width will cause flow-induced surface instabilities to occur at lower flow velocities, (ii) large-amplitude deflections are possible before instability onset via transient growth and (iii) the amplitude of instability induced surface oscillations increases as channel height decreases.